How the land use/cover changes and environmental factors at different scales affect lake water quality in arid and semi-arid regions - Liu, Xuhua; Liu, Huamin; Jing, Jin; Liu, Yang; Xu, Zhichao; Cao, Xiaoai; Ma, Linqian; Zhuo, Yi; Wen, Lu; Wang, Lixin (Frontiers in Ecology and Evolution, 2023)
The quantitative relationship between land use/cover change (LUCC) within basins, lake water environmental factors, and water quality has long been a popular research area. In this study, we investigated three typical basins (Ulansuhai Basin, Daihai Basin, and Dalinor Basin) in arid and semi-arid areas of China. The assessment was based on the China Land Cover Dataset (CLCD), which was used to calculate the land use dynamic degree index and Markov transfer matrix. Moreover, an econometric analysis model and a hybrid evolutionary algorithm (HEA) model were used to explore the quantitative relationship between LUCC and environmental factors on the lake water quality. The results showed that the LUCC of the three lake basins was dominated by cultivated land and grassland over the past 20 years. In all of the basins, grassland and water area were converted into cultivated land, water area decreased to varying degrees, and impervious surface area increased continuously. Moreover, the concentration of TN and TP were generally proportional to chemical oxygen demand concentration (COD), biochemical oxygen demand concentration (BOD5), and dissolved oxygen concentration (DO), but inversely proportional to water depth and transparency; the relationship between Nutrient concentration and pH was usually related to the ecological threshold. On the basin scale, the grassland and forestland played positive roles in improving water quality, while cultivated land and impervious surface were the main factors contributing to water pollution. Overall, this study provides a scientific theoretical basis for the rational utilization of land resources, improvement of lake water quality, and ecological protection of typical lake basins in arid and semi-arid regions.